Using Arm Coordination Plyometric Exercises For Developing Some Muscular Strength Forms, Response Speed and Epee Touching Accuracy - Nori, Sabah; Fakher, Amer (Journal of Physical Education, 2017)
The problem of the research lies in finding a training aid that incorporates coordination plyometric exercises in epee. The aim of the research was designing coordination plyometric exercises for the arms as well as identifying the effect of these exercises on some muscular strength forms, speed of response and performance accuracy in epee. The researchers hypothesized statistical differences between posttests. The researchers used the experimental method. The subjects were a group of students from physical education and sport sciences College/ Al Mostenseria University. The subjects followed a training program designed by the researchers that included a set of coordination plyometric exercises. The variables of the research were explosive power, power defined by speed, strength endurance, speed of response and touch accuracy. The data was collected and treated using proper statistical operations. The researchers concluded that using coordination plyometric exercises have a positive effect on developing (explosive power, power defined by speed, strength endurance, response speed and touching in epee. Finally the researchers recommended using coordination plyometric exercises in fencing as well as selecting other exercises to develop skill performance in fencing